A sutileza da discriminação de gênero na nomenclatura dos logradouros públicos. Vitória (ES). 1970-2000 - Nader, Penha Mara Fernandes (2007)
The feminist movement, as a social movement reacting to the discriminatory social practices has denounced several forms of diferent treatment against women and influenced several changes in society, struggling towards changes in the way power is imposed. The second wave of the feminist movement in Brazil was constructed in an environment of strong dispute with the Military System and with the traditional values and matches the period of changes in Vitória resulting form the industrialization process that substantially changed the economic, political, social and cultural profile of the Vitória society. This paper discloses the subtle character of the gender discrimination in the naming of public places in Vitória Municipality, which is the capital of the State of Espírito Santo, as the names picked for the streets, avenues and other places - therefore, to remam for posterity - are prevailingly man’s names, covering a signiflcant bias, as it keeps women away from the city history and city memory. lhe Municipal Public Power (Mayor Ship and Representatives) have the legal power to name the city places, however, not always they consider the due proportion between names of men and women at the time of choosing who will be granted the tribute, lhe posthumous homage, as a sign of merít acknowledgement, is not far from the general picture of systematic discrimination of genders that characterizes the socíety that adopted and keeps this universal tradition. Women are not welI remembered by their names in places, as if women were not worthy of receiving such a homage. lhe gender concept, crucial to discuss unbalances between men and women evidences that they are not natural, however product and process in the social and cultural relations, historically built and permeated by power relations.